TERLIBAT DENGAN KEBERAGAMAN: PERSPEKTIF TEOLOGIS TENTANG RELIGIONUM DALAM MASYARAKAT PLURALISTIK - Theopilus Wesly Pongtuluran (CV. Adiba Aisha Amira, 2025)
In the context of an increasingly pluralistic society, interfaith interaction becomes a crucial aspect in creating social harmony. This article explores theological perspectives on religious diversity (religionum) and how it plays a role in a pluralistic society. Using a comparative approach, this article analyzes the basic principles upheld by various religious traditions and identifies significant points of similarity and difference. The main focus is to understand how the theology of each religion responds to and interacts with diversity, and how these values can support interfaith dialogue and social tolerance. The analysis results reveal that despite fundamental differences in teachings and practices, there are universal values that can serve as bridges for dialogue and cooperation. This research also highlights the importance of inclusive and dialogical approaches in addressing issues related to religious pluralism. Thus, it is hoped that these theological insights can contribute to enhancing tolerance and peaceful coexistence in diverse societies.